2021
DOI: 10.1038/s41598-021-97779-2
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between membrane active host defense peptides and heme modulates their assemblies and in vitro activity

Abstract: In the emerging era of antimicrobial resistance, the susceptibility to co-infections of patients suffering from either acquired or inherited hemolytic disorders can lead to dramatic increase in mortality rates. Closely related, heme liberated during hemolysis is one of the major sources of iron, which is vital for both host and invading microorganisms. While recent intensive research in the field has demonstrated that heme exerts diverse local effects including impairment of immune cells functions, it is almos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 88 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Upon prolonged treatment for 4 h and 6 h, among the four strains, the most significant decrease in cell membrane fluidity was observed in the S. enterica ATCC15611 treatment group (4.80-fold and 5.66-fold) ( Figure 2 B). The change in membrane lipid composition may contribute to the observed membrane fluidity change by the therapeutic agents [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Upon prolonged treatment for 4 h and 6 h, among the four strains, the most significant decrease in cell membrane fluidity was observed in the S. enterica ATCC15611 treatment group (4.80-fold and 5.66-fold) ( Figure 2 B). The change in membrane lipid composition may contribute to the observed membrane fluidity change by the therapeutic agents [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Impaired membrane integrity occurs due to the interaction of AMP with a negatively charged cell membrane, inhibition of protein, DNA, and RNA synthesis, or interaction with specific intracellular targets [ 22 , 24 , 27 ]. The critical interaction points between the peptide and the bacterial membrane are electrostatic forces between the cationic AMPs and the negatively charged bacterial surface [ 28 , 29 , 30 ]. The cytoplasmic membranes of Gram-positive and Gram-negative bacteria are rich in phospholipids, phosphatidylglycerol, and cardiolipin, which have negatively charged major groups which strongly attract positively charged AMPs [ 1 , 31 ].…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…Inversely, the attenuation of specific fusion activity is also important as in the case of viral entry, where inhibitory membrane-active peptides, e.g., in the drug Fuzeon, demonstrate the potential of peptides interfering with membrane processes. As a natural inspiring example where peptidic self-assembly plays a key role in membrane manipulation, antimicrobial peptides often form temporary, assembled constructs that could be highly relevant for exerting toxicity on targets or for modulating other related biological functions. Recently, it has also been indicated that the manipulation of their membrane activity and thus their antimicrobial affinity can also be achieved by the formation of functional supramolecular coassemblies. ,, However, these constructs often adopt only partially ordered assemblies, which limits their controlled use as functional materials.…”
Section: Introductionmentioning
confidence: 99%